Nouvelle économie du développement et essais cliniques randomisés : une mise en perspective d’un outil de preuve et de gouvernement - Agnès Labrousse (Revue de la Régulation)
This article tries to shed some light on the remarkable take-off of randomized controlled experiments in development economics, both as an instrument of proof and as an instrument of government. This technology transfer from clinical studies makes a decisive contribution to mainstream development economics by instilling a welcome concreteness into the core of the analysis, far away from the late Washington consensus. Whereas this technique of proof is largely consolidated now, the embeddedness of this novel instrument in a wider epistemological framework (type of inference, relationship to theory, modes of generalization and relation to historical specificity) remains often fragmentary, leading to some blank spots and limits. Like randomized clinical experiments, it is a social construct and not a purely objective technique. It is an instrument of proof but also a trendy instrument of government – in the Foucaldian sense. Its manifold applications remind of other forms of social engineering and belong to a type of governmentality noticeably distinct from the neoliberal tradition.